1999
DOI: 10.1111/1469-7610.00541
|View full text |Cite
|
Sign up to set email alerts
|

Parents' Judgements About Young Children's Problems: Why Mothers and Fathers Might Disagree Yet Still Predict Later Outcomes

Abstract: Correlates of parents' ratings of behavioural problems were explored in a sample of 93 British families, in which mothers and fathers rated their children at the time of the fourth birthday on the Achenbach Child Behavior Checklist. As in other samples, there was moderate convergence in mothers' and fathers' total problem scores, but also signs that they were reporting different sorts of problems linked to different influences. The father's rating was primarily associated with the child's cognitive ability. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
45
1
2

Year Published

2001
2001
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(52 citation statements)
references
References 25 publications
4
45
1
2
Order By: Relevance
“…Previous findings suggested that parents' reports, although valuable, may be biased based upon personal factors (e.g., depression, Hay et al, 1999) and by past experiences with the child (Patterson, 1982), whereas an observational approach is thought to offer a-less biased-ecologically valid alternative. Also, whereas the SNAP paradigm assesses disruptive behavior in a highly specific context at a specific time, questionnaires such as the SCBE-30 provide global ratings of everyday behavior across a wide range of contexts and a large time frame.…”
Section: Discussionmentioning
confidence: 99%
“…Previous findings suggested that parents' reports, although valuable, may be biased based upon personal factors (e.g., depression, Hay et al, 1999) and by past experiences with the child (Patterson, 1982), whereas an observational approach is thought to offer a-less biased-ecologically valid alternative. Also, whereas the SNAP paradigm assesses disruptive behavior in a highly specific context at a specific time, questionnaires such as the SCBE-30 provide global ratings of everyday behavior across a wide range of contexts and a large time frame.…”
Section: Discussionmentioning
confidence: 99%
“…A hipótese para essa diferença é que elas convivem mais tempo com os filhos(as), estando mais expostas às situações em que o comportamento pode ser observado. Outra hipótese está relacionada às diferentes maneiras com que as crianças tendem a se comportar na presença dos pais ou das mães que, por sua vez, irão observar filhos(as) de maneira distinta (Hay, Sharp, Pawlby, & Schmücker, 1999). Este dado pode explicar, por exemplo, o fato das mães reportarem mais problemas de comportamento de suas crianças do que os pais (Duhig e cols., 2000).…”
Section: Introductionunclassified
“…1 Informant discrepancies have been found in virtually every method of clinical assessment that researchers and practitioners use to assess abnormal behavior in youths (e.g., rating scales, structured interviews; Achenbach et al, 1987;Grills & Ollendick, 2002). Moreover, discrepancies have been found in samples of informants encompassing diverse ethnic and cultural backgrounds (Hay et al, 1999;Jensen et al, 1999;Kaufman, Swan, & Wood, 1980;Krenke & Kollmar, 1998;Rohde et al, 1999;Rousseau & Drapeau, 1998;Verhulst, Althaus, & Berden, 1987) and in virtually any clinic sample in which discrepancies have been examined (Edelbrock, Costello, Dulcan, Conover, & Kala, 1986;Frank, Van Egeren, Fortier, & Chase, 2000;Frick, Silverthorn, & Evans, 1994;Hart, Lahey, Loeber, & Hanson, 1994;Kazdin, French, & Unis, 1983;Rapee, Barrett, Dadds, & Evans, 1994).…”
mentioning
confidence: 99%